Testosterone level and risk of type 2 diabetes in men: a systematic review and meta-analysis. Issue 1 (January 2018) - Yao, Qiu-ming; Wang, Bin; An, Xiao-fei; Zhang, Jin-an; Ding, Liumei
Abstract : Background: Type 2 diabetes is a risk factor for testosterone deficiency and impaired sex steroid status. Some studies also investigated the association of testosterone level with diabetes risk in men, but reported controversial findings. To clarify this issue, we conducted a systematic review and meta-analysis. Methods: PubMed, EMBASE and Web of Science were searched for eligible cohort or nested case–control studies published up to August 15, 2017. Meta-analysis was used to calculate the pooled relative risk (RR) of type 2 diabetes associated with higher testosterone level. Results: Thirteen cohort or nested case–control studies with 16, 709 participants were included. Meta-analysis showed that higher total testosterone level could significantly decrease the risk of type 2 diabetes in men (RR = 0.65; 95% CI 0.50–0.84; P  = 0.001), and higher free testosterone level could also decrease the risk of type 2 diabetes in men (RR = 0.94; 95% CI 0.90–0.99; P  = 0.014). After excluding two studies that did not calculate RRs by quartiles of testosterone levels, both higher total testosterone and free testosterone levels could decrease the risk of type 2 diabetes in men, and the pooled RRs were 0.62 (95% CI 0.51–0.76; P  < 0.001) and 0.77 (95% CI 0.61–0.98; P  = 0.03), respectively. Conclusion: This meta-analysis suggests that higher testosterone level can significantly decrease the risk of type 2 diabetes in men. Therefore, combined with previous researches, the findings above suggest a reverse-causality scenario in the relation between testosterone deficiency and risk of type 2 diabetes in men.